(untitled) (Confluenţe Bibliologice, 2025)
Scientiﬁc Library keeps rare collection of theological, moral and religious periodicals, mostly donated from Vasile Ioan Nicorici , inhabitant of mun. Balti. The donation amount 750 documents in 694 titles, including 86 periodicals in 8 titles. Through this work we aimed to achieve a description of religious and theological periodicals, which is of great scientiﬁc value both for students and teachers and for various researchers.